Delayed onset of ocean acidification in the Gulf of Maine - Joseph A. Stewart; Branwen Williams; Michèle LaVigne; Alan D. Wanamaker; Aaron L. Strong; Brittany Jellison; Nina M. Whitney; Diana L. Thatcher; Laura F. Robinson; Jochen Halfar; Walter Adey (Scientific Reports)
Abstract The Gulf of Maine holds significant ecological and economic value for fisheries and communities in north-eastern North America. However, there is apprehension regarding its vulnerability to the effects of increasing atmospheric CO2. Substantial recent warming and the inflow of low alkalinity waters into the Gulf of Maine have raised concerns about the impact of ocean acidification on resident marine calcifiers (e.g. oysters, clams, mussels). With limited seawater pH records, the natural variability and drivers of pH in this region remain unclear. To address this, we present coastal water pH proxy records using boron isotope (δ11B) measurements in long-lived, annually banded, crustose coralline algae (1920–2018 CE). These records indicate seawater pH was low (~ 7.9) for much of the last century. Contrary to expectation, we also find that pH has increased (+ 0.2 pH units) over the past 40 years, despite concurrent rising atmospheric CO2. This increase is attributed to an increased input of high alkalinity waters derived from the Gulf Stream. This delayed onset of ocean acidification is cause for concern. Once ocean circulation-driven buffering effects reach their limit, seawater pH decline may occur swiftly. This would profoundly harm shellfisheries and the broader Gulf of Maine ecosystem.